Fire safety education for children at TKK IPEKA Pluit - Setiawan, sigit (Yayasan Putra Adi Dharma, 2024)
On October 10, 2023, the Fire Department (Damkar) conducted a fire safety education program at TKK IPEKA Pluit to educate young children about fire prevention and emergency procedures. This initiative aimed to instill basic fire safety knowledge in students, including the use of firefighting equipment and safe evacuation procedures. The interactive approach, involving simulations and storytelling, engaged the children effectively. Teachers and staff also received training to handle emergencies competently. The program ensured the availability and functionality of fire safety equipment throughout the school. Continuous collaboration with Damkar provided valuable guidance and evaluation, enhancing the program's effectiveness. As a result, there was a significant improvement in the children’s understanding and readiness for fire emergencies. This program not only heightened fire safety awareness within the school community but also established TKK IPEKA Pluit as a model for implementing comprehensive and effective fire safety education